2017
DOI: 10.1139/cjfas-2016-0203
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Chinook salmon consumption in Washington State inland waters by four marine mammal predators from 1970 to 2015

Abstract: Conflicts can arise when the recovery of one protected species limits the recovery of another through competition or predation. The recovery of many marine mammal populations on the west coast of the United States has been viewed as a success; however, within Puget Sound in Washington State, the increased abundance of three protected pinniped species may be adversely affecting the recovery of threatened Chinook salmon (Oncorhynchus tshawytscha) and endangered killer whales (Orcinus orca) within the region. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 58 publications
1
69
0
Order By: Relevance
“…We speculate that the synergistic effects of habitat loss (Good et al., ), long‐term increases in predator abundance (Chasco et al., ), and poor water quality (Meador, ) contributed to the lack of covariation in survival among Salish Sea Chinook salmon populations. Magnusson and Hilborn () observed higher early marine survival of coastal Oregon hatchery Chinook salmon in more pristine estuaries.…”
Section: Discussionmentioning
confidence: 92%
“…We speculate that the synergistic effects of habitat loss (Good et al., ), long‐term increases in predator abundance (Chasco et al., ), and poor water quality (Meador, ) contributed to the lack of covariation in survival among Salish Sea Chinook salmon populations. Magnusson and Hilborn () observed higher early marine survival of coastal Oregon hatchery Chinook salmon in more pristine estuaries.…”
Section: Discussionmentioning
confidence: 92%
“…Commonly hypothesized causes of change in salmon age‐size structure include (i) size‐selective harvest, (ii) environmental change such as changes in temperature regimes or ocean productivity that affect growth and mortality rates, and (iii) impacts of hatchery practices and increased competition for food (including non‐Chinook hatchery populations). A previously overlooked hypothesis attributes the observed changes to (iv) predation by marine mammals, especially a growing number of resident killer whales and their size‐selective predation on Chinook salmon (Chasco, Kaplan, Thomas, Acevedo‐Gutiérrez, Noren, Ford, & Marshall, ; Chasco, Kaplan, Thomas, Acevedo‐Gutiérrez, Noren, Ford, & Shelton, ). In the following, we present these hypotheses in detail and discuss their qualitative consistency with the findings reported in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these predators have increased in abundance in coastal waters of the Northeast Pacific during the past decades, primarily due to harvest bans established since the 1970s by the US Marine Mammal Protection Act and the US Endangered Species Act (Magera, Flemming, Kaschner, Christensen, & Lotze, ). A recent study estimated that consumption of Chinook salmon biomass by marine mammals, including pinnipeds and killer whales, has nearly tripled since the mid‐1970s (Chasco, Kaplan, Thomas, Acevedo‐Gutiérrez, Noren, Ford, & Marshall, ; Chasco, Kaplan, Thomas, Acevedo‐Gutiérrez, Noren, Ford, & Shelton, ). Predation by pinnipeds, however, is unlikely to cause declines in the average age and size of adult fish, because these predators mostly select large juvenile and small adults, do not show a preference for Chinook salmon compared to other salmonids and are mostly concentrated near river mouths (Adams et al., ; Thomas, Nelson, Lance, Deagle, & Trites, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, the observed decrease in body mass of Puget Sound salmon and steelhead over the last four decades coincides with observed trends from other locations in addition to changing environmental conditions and anthropogenic factors in the Puget Sound freshwater and marine habitats. These include dramatic increases in the number of humans living near the Sound, increased marine mammal predation (Chasco et al, ), changes in hatchery salmon and steelhead production (HSRG, ), increased shoreline armouring (Habitat Strategic Initiative et al, ; Morrison et al, ), changes in the frequency of El Nino events (Wolter & Timlin, ), changes in herring, other forage fish, and jellyfish abundance and distribution (Greene, Kuehne, Rice, Fresh, & Penttila, ; Siple & Francis, ; Siple et al, ) and increased total salmon abundance in the Sound (as reported here). Each of these factors may have influenced growth and feeding conditions and thus body size of Puget Sound salmon and steelhead in a variety of ways, as they have been shown for these species in other areas within and outside the Salish Sea (Debertin et al, ; Jeffrey et al, ).…”
Section: Discussionmentioning
confidence: 99%